Characterization of the Portuguese SSS into the Europe: A Contribution - Pereira, Maria Teresa Ribeiro (2015)
Nowadays, Short Sea Shipping (SSS) is an essential part in European multi-modal transport system, representing approximately thirty-seven per cent of intra-Community transactions in tonnes per kilometre (tkm). Since 2001, the European Shortsea Network (ESN) in partnership with the short-sea Promotion Centres (SPC) of each Member State of the European Union (EU) have managed to make significant progress in the promotion and development of this mode of transport.This paper aims to assess and analyse the SSS of containerised goods in Portugal and its articulation with other EU routes and also other transport modes. The current SSS infrastructure, how the sector is organized, as well as the future perspectives for the sector are also analysed for the case of Portugal.The analyses are based on a survey that was carried out on the logistics operators, navigation agents, freight forwarders, and the leading imports and exports manufacturers in Portugal.